VD_FINDINFO HC / 2015 / 100 vom 20. Januar 2015 - VD Tribunal cantonal (2015)
PROTECTION DE L'UNION CONJUGALE, CONJOINT, ENFANT, OBLIGATION D'ENTRETIEN, DROIT DE GARDE, EXPERTISE | 163 al. 1 CC, 176 al. 1 ch. 1 CC, 176 al. 3 CC, 179 al. 1 CC, 273 CC, 152 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 317 al. 1 CPC (CH), 317 al. 2 CPC (CH)